Entrepreneurship and sustainability : do they have anything in common? - Gaweł, Aleksandra (Economics and Business Review, 2012)
The main aim of this paper, within a conceptual approach, is to show the possible relationship between entrepreneurship, especially entrepreneurial orientation, and sustainability. The entrepreneurial orientation of companies (measured by their innovativeness, proactiveness, risk-taking, autonomy and competitive aggressiveness) and sustainable development are not mutually exclusive. Entrepreneurial orientation is more a particular way of acting whereas sustainability is a set of postulates and aims. Thus, in order for a favourable relationship to exist between the two, implementing the pro-social and pro-ecological postulates of sustainability must provide measurable benefits for a company and must be incorporated into a company's strategy. (original abstract)